Potensi Remap STAD (Reading Concept Mapping Student Teams Achievement Division) untuk Meningkatkan Keterampilan Berpikir Kritis Siswa - Farqiyatur Ramadhan; Susriyati Mahanal; Siti Zubaidah (Universitas Sebelas Maret, 2016)
Critical thinking skills needed in learning process to train students to solve problems. In addition, the 21st century need the individuals who have analytical and critical thinking. To prepare students to face the challenges of 21st century life, the critical thinking skills need to be developed. Empowering critical thinking skills can be done through the implementation of Remap STAD learning models. Remap STAD can enhance students' critical thinking skills because it was required students to read in advance, so the students will be trained to read. After reading activity students make a concept map from what they have been read. Furthermore, using Remap STAD learning models can enhance students' thinking skills beacuse students can share their idea in group work. Kata kunci: Remap STAD, Critical Thinking